Structure, dielectric, ferroelectric, and magnetic properties of (1 − x) BiFeO3–x (Ba0.85Ca0.15)(Zr0.10Ti0.90)O3 ceramics. (June 2015) - Yi, Jing; Tian, Ye; Wei, Lingling; Li, Junwei; Liang, Pengfei; Shi, Pingping; Chao, Xiaolian; Yang, Zupei
Graphical abstract: Highlights: BFO–BCZT ceramics transformed from rhombohedral to pseudocubic with increasing x . The electrically heterogeneous microstructure is caused by the IBLC effects. The optimal ferroelectric and magnetic properties were obtained at 0.30 ≤ x ≤ 0.35. Abstract: Polycrystalline (1 − x ) BiFeO3 – x (Ba0.85 Ca0.15 )(Zr0.10 Ti0.90 )O3 [(1 − x ) BFO − x BCZT)] ceramics were fabricated by a solid state reaction method. The phase structure, microstructure, and dielectric, ferroelectric and magnetic properties of the (1 − x ) BFO − x BCZT ceramics were systematically investigated. The crystal structure of the (1 − x ) BFO − x BCZT ceramics transformed from rhombohedral to pseudocubic with increasing x . A morphotropic phase boundary existed at the composition of 0.20 ≤ x ≤ 0.30. The average grain size of the ceramics initially increased to a maximum at x = 0.30 and then decreased. The frequency dependence of dielectric constant and complex impedance plots indicated an electrically heterogeneous microstructure for x ≤ 0.20 caused by the coexistence of Fe 2+ and Fe 3+ . T m and ϵ m decreased with increasing x for 0.25 ≤ x ≤ 0.80, and the hysteresis loops ( P–E ) became slimmer with increasing x . All samples presented weak ferromagnetic ordering, indicating that the substitution of BCZT into the BFO matrix released its potential magnetization. The optimal ferroelectric and magnetic properties, P r of 22.7–27.3 μC/cm 2 and M r of 0.0394–0.0744 emu/g, were obtained at 0.30 ≤ x ≤ 0.35.